Reparation demands and collective guilt assignment of black South Africans - Dumont, K.; Waldzus, S. (Journal of Black Psychology, 2017)
The present research studied reparation demands of born-free Black South African adolescents as members of a former victimized group from a social psychological perspective. Two cross-sectional studies tested whether identification indirectly predicts reparation demands via assignment of collective guilt to White South Africans; and whether this indirect relation is moderated by cross-group friendship. The results support both hypotheses and show a stronger link between identification with the victimized group and collective guilt assignment in a segregated rather than a desegregated context (Study 1: N = 222) and for participants reporting lower levels of cross-group friendship (Study 2: N = 145). Reparation demands are important for strongly identified members of a victimized group in a postconflict situation. Their mediation by collective guilt assignment, mitigated by cross-group friendship, indicates that one major function is to insure recognition of the victims’ past suffering and to repair the relationship rather than ostracizing the transgressor group or gaining access to resources.